The Economic Consequences of the Brexit Vote - Benjamin Born; Gernot Müller; Moritz Schularick; Petr Sedláček (Center for Economic Studies and ifo Institute (CESifo), 2017)
The unexpected outcome of the Brexit vote in June 2016 provides a rare macroeconomic experiment to study the aggregate consequences of a sudden change in expectations regarding future economic prospects. Using synthetic control methods, we show that forward looking households and businesses lowered spending in response to the vote, causing an output loss of more than 1 percent. Heightened economic policy and macroeconomic uncertainty explain close to half of the observed output loss. But a large part of the consequences of the vote also reflects a downgrade of expectations about long-run income, not only a wider dispersion of potential outcomes.
Keywords: E65; F13; F42; 330; Brexit; European Union; synthetic control method; VAR; anticipation effects; economic policy uncertainty; macroeconomic uncertainty